P.100 A Retrospective Study of Alberta Emergency Room Utilization by Pediatric Epilepsy Patients. (November 2021) - Kassiri, J; Mailo, J; Rajapakse, T; Wang, GT; Liu, N; Richer, L; Sinclair, DB
Abstract : Background: Epilepsy, a common neurologic condition, instigates a large number of emergency room (ER) visits annually. This project aims to retrospectively review the patterns and characteristics of Alberta ER visits by pediatric epilepsy patients. Methods: Methods: Alberta Health administrative databases, including the Inpatient Discharge Abstract Database, the National Ambulatory Care Reporting System, Diagnostic Imaging and Medical Laboratory, were used to identify ER utilization patterns among children with epilepsy in Alberta, Canada between 2012–2018. Results: Results: Of 5, 419 pediatric epilepsy ER patients between 2012–2018 in Alberta, 59% were developmentally delayed children. Children in this particular group, when compared to developmentally normal children with epilepsy, had the following characteristics: they were significantly more likely to utilize ERs in children's hospitals versus other hospitals; they presented at a significantly younger age; they had a significantly longer length of stay; they had higher triage scores; they were subjected to significantly more investigations; and they had significantly more hospital admissions for epilepsy. Conclusions: Discussion: This novel Alberta-wide study of resource utilization of pediatric epilepsy patients shows that developmentally delayed children with epilepsy use significantly higher resources compared to developmentally normal children with epilepsy. Whether this is justified or not requires further study.